2016
DOI: 10.1103/physreva.94.062508
|View full text |Cite
|
Sign up to set email alerts
|

Multiconfiguration calculations of electronic isotope shift factors in Al i

Abstract: The present work reports results from systematic multiconfiguration Dirac-Hartree-Fock calculations of electronic isotope shift factors for a set of transitions between low-lying levels of neutral aluminium. These electronic quantities together with observed isotope shifts between different pairs of isotopes provide the changes in mean-square charge radii of the atomic nuclei. Two computational approaches are adopted for the estimation of the mass-and field-shift factors. Within these approaches, different mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…the "MR-SD" model. It was shown that this method is capable of accounting for the electron correlation for the complex ions and atoms [32,[39][40][41][42][43].…”
Section: Computational Modelmentioning
confidence: 99%
“…the "MR-SD" model. It was shown that this method is capable of accounting for the electron correlation for the complex ions and atoms [32,[39][40][41][42][43].…”
Section: Computational Modelmentioning
confidence: 99%
“…It is important to mention that core-core (CC) contributions, i.e., unrestricted SD substitutions from core orbitals, are not accounted for, contrary to the strategy adopted in the papers on Mg I [37] and Al I [38]. Indeed, the CSF expansions in Zn I become too large when CC correlations within the complete 2s 2 2p 6 3s 2 3p 6 3d 10 core orbitals are added to the nl = 9h AS, counting for the J π = 2 − state more than 10 8 CSFs for the SrD-MR and SrDT-SS models.…”
Section: Srdt-ss Modelmentioning
confidence: 99%
“…[37,38,52]. Hence, neglecting CC contributions enables us to use separate orbital basis sets, in which orbital relaxation is allowed.…”
Section: Srdt-ss Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach of an active space expansion using a multireference has been previously described in Refs. [36,37]. Based on this reference set, single and double excitations from the 4p, 4d, 5s, and 5p orbitals to correlation orbitals nl with l g were considered.…”
Section: Theoretical Calculationsmentioning
confidence: 99%